Mapping of areas for coffee cultivation on terraces in Minas Gerais – Brazil (Research, Society and Development, 2025)
Brazil is the largest producer and exporter of coffee globally, with Minas Gerais accounting for over 50 % of national production. However, sustainable coffee production in the mountainous areas of Minas faces challenges such as soil erosion, low mechanization, and labor shortages. The use of agricultural terraces has emerged as a viable solution in these regions, helping to mitigate some of these issues. This study aimed to map areas in Minas Gerais with potential for cultivating Arabica coffee in terraces, considering technical factors such as altitude, slope, soil, temperature, precipitation, and humidity. Using QGIS and geoprocessing techniques, spatial data were integrated, and an analysis of the ideal, intermediate, and unsuitable ranges for cultivation was conducted. The process involved applying intersection and overlay commands on the layers to identify suitable areas. The results indicated that approximately 442,000 hectares fall within the ideal range, while 1.92 million hectares are within the intermediate range for implementing the terrace system. Additionally, in already cultivated areas, about 43,000 hectares are suitable for terrace cultivation in the ideal range, and 60,000 hectares in the intermediate range. These results expand management options for producers in mountainous regions, although further research is needed on the costs and environmental impacts of this practice.